Analyzing the Shape of the Upper Part on the Middle-Aged Male Body in Ho Chi Minh City – Vietnam - Nguyen, Mau Tung; Tran, Thi Minh Kieu; Pham, Thi Thao; Pham, The Bao (Old Journal, 2020)
The cross-sectional research method was used to analyze the shape of the upper body of middle-aged men. The 3D anthropometric measurements data was collected from 378 different men aged 30-60 in HCMC by using the 3D Size Stream Body Scanner. Later the data was processed by statistical probability math and SPSS 25 software. The statistics indicate that most of the surveyed people have higher left shoulder height than their right shoulder height. The increase in circumference indexes leads to the wide index of the circumference increase. As people get older, their body height tends to decrease. The older people get, the bigger their chest size and waist size circumference indexes become with the front part increases more than the back part.